3D simulation: an effective tool based on an anthropocentric approach and its application in kitchen design. (1st January 2012) - Leborgne, Cédric; Roussel, Benoit; Millet, Dominique; Aoussat, Améziane
Ergonomists are faced with two main challenges in terms of the innovative design: the discrepancy between activity and uses and the paradox of design ergonomics. Our anthropocentric approach proposes a method by which the design ergonomist may best identify customer needs and expectations and take them into account when designing innovative products. In order to study them as yet non-existents, we analyse the results of introducing an activity simulation tool in order to anticipate future possible uses of such products. The case study developed in this work is a kitchen design project, and one of the main contributions is the re-conceptualisation of the activity analysis, to a 'lozenge layout' which allows to reduce the distance covered by kitchen users. The results also contribute to the design process improvement and the possibility of exploring innovative alternatives in the simulation tool proposed in this work.